MXene Key Composites: A New Arena for Gas Sensors - Wang, Yitong; Wang, Yuhua; Jian, Min; Jiang, Qinting; Li, Xifei (Nano-Micro Letters, 2024)
With the development of science and technology, the scale of industrial production continues to grow, and the types and quantities of gas raw materials used in industrial production and produced during the production process are also constantly increasing. These gases include flammable and explosive gases, and even contain toxic gases. Therefore, it is very important and necessary for gas sensors to detect and monitor these gases quickly and accurately. In recent years, a new two-dimensional material called MXene has attracted widespread attention in various applications. Their abundant surface functional groups and sites, excellent current conductivity, tunable surface chemistry, and outstanding stability make them promising for gas sensor applications. Since the birth of MXene materials, researchers have utilized the efficient and convenient solution etching preparation, high flexibility, and easily functionalize MXene with other materials to prepare composites for gas sensing. This has opened a new chapter in high-performance gas sensing materials and provided a new approach for advanced sensor research. However, previous reviews on MXene-based composite materials in gas sensing only focused on the performance of gas sensing, without systematically explaining the gas sensing mechanisms generated by different gases, as well as summarizing and predicting the advantages and disadvantages of MXene-based composite materials. This article reviews the latest progress in the application of MXene-based composite materials in gas sensing. Firstly, a brief summary was given of the commonly used methods for preparing gas sensing device structures, followed by an introduction to the key attributes of MXene related to gas sensing performance. This article focuses on the performance of MXene-based composite materials used for gas sensing, such as MXene/graphene, MXene/Metal oxide, MXene/Transition metal sulfides (TMDs), MXene/Metal–organic framework (MOF), MXene/Polymer. It summarizes the advantages and disadvantages of MXene composite materials with different composites and discusses the possible gas sensing mechanisms of MXene-based composite materials for different gases. Finally, future directions and inroads of MXenes-based composites in gas sensing are presented and discussed. Highlights: 1 With its layered structure, abundant functional groups, and excellent electrical conductivity, MXene is of great research interest in the field of gas sensing. 2 The preparation technology of gas sensors is constantly being optimized, opening up avenues for the development of gas sensing. 3 MXene-based composite materials (MXene/graphene, MXene/metal oxides, MXene/MOF, and MXene/polymer) are applied in various gas sensors.